Implementation of reflective practice programme for registered nurses - N. Nelumbu, Lucia (International Journal of Advanced Nursing Studies, 2015)
The researcher was convinced that the development of a programme is the good idea that will enhance the proper application of reflective practice in clinical settings for nurses not simply to perform daily routine activities without paying attention to reflection. The developed programme was implemented through a two-day workshop.Â  Therefore, the researcher considered the workshop to be an ideal strategy for implementation, because reflection can only be facilitated and practiced through active participation. The participants were drawn from various disciplines such as: Paediatrics, Surgery, Gynecology and Obstetrics and Internal Medicine. The facilitator explained the purpose of the workshop and the rules to be followed during the workshop. The content of the programme was presented and discussed during the specific sessions as it was scheduled. After the sessions, the participants were informed that they have to go back and apply what they learned from the workshop during their clinical practice for three months. And after three months the facilitator together with the participants contacted the evaluation of the application of the content of the programme.